Allometric models for above and below-ground biomass of wild Musa stands in tropical semi evergreen forests - Sabina Yasmin Laskar; Gudeta Weldesemayat Sileshi; Arun Jyoti Nath; Ashesh Kumar Das (Global Ecology and Conservation, 2020)
Wild Musa species constitute an important component of tropical rain forests, wet evergreen forests and deciduous forests. Unlike forest trees, biomass estimation models are virtually lacking for wild Musa species. The present study aimed to determine whether growth and biomass accumulation in Musa species follow simple allometric scaling rules; and to develop allometric models for estimation of biomass storage in wild Musa balbisiana stands. A total of 156, M. balbisiana plants were harvested for above and below ground biomass for developing the biomass estimation models. The commonly used height-diameter (H-D) models: Chapman-Richard, exponential, Gompertz, hyperbolic, Michaelis-Menten (saturation growth), power-law, Weibull and Von Bertalanffy functions were used to predict missing heights from field measurement of plant diameter. The performance of the power-law model involving D alone, pseudo-stem height (Hp) alone or a combination of D and Hp was used to develop the best biomass estimation model. Nonlinear seemingly unrelated regression (NSUR) was used to model total biomass stocks. The stand density and basal area of the wild Musa stand was 14900 pseudo-stem ha−1, and 14.94 m2 ha−1, respectively. Based on the goodness of fit criteria, Hp, and D at 130 cm, the Exponential and Gompertz functions were observed to be the two best models for describing H-D relationship. A model containing D and Hp was found to be the best model for total biomass estimation in M. balbisiana. The total biomass stock predicted by our best NSUR model was 90.7 Mg ha−1, of which 55.4 Mg ha−1 was found in above-ground and 34.7 Mg ha−1 in below-ground plant parts. The present study suggests wild M. balbisiana hold significant potential to contribute to stand level biomass stock in forest ecosystems where they occur mixed with trees.